3D porous chitosan-alginate scaffold stiffness promotes differential responses in prostate cancer cell lines. (October 2019) - Xu, Kailei; Ganapathy, Kavya; Andl, Thomas; Wang, Zi; Copland, John A.; Chakrabarti, Ratna; Florczyk, Stephen J.
Abstract: Prostate cancer (PCa) is a leading cause of death for men worldwide. Most PCa patients die from metastasis and bone is the most common metastatic site. Three dimensional (3D) porous chitosan-alginate (CA) scaffolds were developed for bone tissue engineering and demonstrated for culture of cancer cells and enrichment of cancer stem cells. However, only a single scaffold composition was studied. Three compositions of 3D porous CA scaffolds (2, 4, and 6 wt%) were used to investigate the effect of scaffold stiffness on PCa cell response with PC-3, C4-2B, and 22Rv1 cell lines. The PC-3 cells formed cell clusters while the C4-2B and 22Rv1 cells formed multicellular spheroids. The three cell lines demonstrated stiffness independent cell growth and expressed phenotypic PCa biomarkers. The osteoblastic PCa lines C4-2B and 22Rv1 mineralized in basal media, while the osteolytic PC-3 line did not, demonstrating that CA scaffold cultures revealed differences in PCa phenotypes. The CA scaffolds are a 3D culture platform that supports PCa growth and phenotypic expression with adjustable scaffold stiffness to mimic stages of metastatic progression. Further investigation of the scaffolds for co-culture of PCa cells with fibroblasts and primary PCa cell culture should be conducted to develop a platform for screening chemotherapies. Graphical abstract: Image 1 Highlights: Three CA scaffold compositions were prepared with different scaffold stiffness. PC-3, C4-2B, and 22Rv1 cell lines had stiffness independent growth in CA scaffolds. Osteoblastic lines C4-2B and 22Rv1 mineralized, while osteolytic PC-3 line did not.